2018
DOI: 10.1016/j.stemcr.2018.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing Nodal Signaling Activity Predisposes Ectodermal Differentiation of Epiblast Stem Cells

Abstract: SummaryThe molecular mechanism underpinning the specification of the ectoderm, a transient germ-layer tissue, during mouse gastrulation was examined here in a stem cell-based model. We captured a self-renewing cell population with enhanced ectoderm potency from mouse epiblast stem cells (EpiSCs) by suppressing Nodal signaling activity. The transcriptome of the Nodal-inhibited EpiSCs resembles that of the anterior epiblast of embryonic day (E)7.0 and E7.5 mouse embryo, which is accompanied by chromatin modifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…In analogy with our previous work creating gastrulation-stage patterns in vitro, we reasoned that geometrically confined hESCs treated with appropriately timed exogenous stimuli would create selforganized patterns of fates within the ectodermal germ layer. In both model organisms and embryonic stem cells, Nodal inhibition has been shown to be crucial for preventing mesendoderm differentiation, allowing cells to adopt ectodermal fates, while BMP signaling is responsible for generating the dorsalventral pattern within the ectoderm (Li et al, , 2015Liu et al, 2018). Thus, we hypothesized that following a two-stage protocol where hESCs are initially induced by Nodal inhibition and subsequently stimulated by BMP4 would cause them to exclusively adopt ectodermal fates.…”
Section: Determining the Window Of Competence For Ectodermal Patterningmentioning
confidence: 99%
See 2 more Smart Citations
“…In analogy with our previous work creating gastrulation-stage patterns in vitro, we reasoned that geometrically confined hESCs treated with appropriately timed exogenous stimuli would create selforganized patterns of fates within the ectodermal germ layer. In both model organisms and embryonic stem cells, Nodal inhibition has been shown to be crucial for preventing mesendoderm differentiation, allowing cells to adopt ectodermal fates, while BMP signaling is responsible for generating the dorsalventral pattern within the ectoderm (Li et al, , 2015Liu et al, 2018). Thus, we hypothesized that following a two-stage protocol where hESCs are initially induced by Nodal inhibition and subsequently stimulated by BMP4 would cause them to exclusively adopt ectodermal fates.…”
Section: Determining the Window Of Competence For Ectodermal Patterningmentioning
confidence: 99%
“…Although we expect these fates to be spatially disorganized in standard culture, this would provide a starting point for micropatterning experiments that test whether geometric confinement leads to ordered emergence of the same set of fates. Previous work in mouse and hESCs, has shown that prolonged Nodal inhibition leads to commitment to the neural fate (Li et al, 2015;Liu et al, 2018;Smith et al, 2008), so we specifically sought a temporal window in which cells are committed to the ectoderm but not exclusively to neural fates.…”
Section: Determining the Window Of Competence For Ectodermal Patterningmentioning
confidence: 99%
See 1 more Smart Citation
“…while Oct4 and Sox2 mRNA levels were largely unchanged. Expression of the additional 266 SB43152-inhibitable mEpiSC markers Fgf5 and T (Liu et al, 2018) were also reduced by EtOH 267 treatment ( Figure 2C). In contrast, EtOH did not alter levels of Lefty1 or Lefty2 in mEpiSC to differences in SB43152 vs. EtOH treatment, or differences in half-lives of these mRNAs in (e.g., HoxA1, Six1, and Gbx2) was observed in hESCs treated with SB43152 for 2 -6 days 274 (Chng et al, 2010;Vallier et al, 2009).…”
mentioning
confidence: 90%
“…Treatment of hESC or mEpiSC cultures with the ALK4 inhibitor, SB43152, led to reduction of 256 Activin/Nodal target gene expression and, eventually, induction of early markers of 257 neuroectoderm differentiation (Chng et al, 2010;Li et al, 2015;Liu et al, 2018;Vallier et al, (Vallier et al, 2009). We assessed expression of these five genes 263 in mEpiSCs treated with EtOH for 6 hours ( Figure 2C).…”
mentioning
confidence: 99%